PHILOSOPHICAL VIEWS OF IBN SINA IN QURANIC EXEGESIS (ON THE EXAMPLE OF SURAH AL IKHLAS) (World Bulletin of Social Sciences, 2026)
This article examines Abu Ali Ibn Sinas philosophical approach to the exegesis of the Quran with particular focus on his interpretations of Surah Al Ikhlas. Ibn Sina sought to explain Quranic verses on the basis of logical and philosophical reasoning and his exegetical method was further developed by later commentators.